2019
DOI: 10.1111/pce.13450
|View full text |Cite
|
Sign up to set email alerts
|

Responses to K deficiency and waterlogging interact via respiratory and nitrogen metabolism

Abstract: K deficiency and waterlogging are common stresses that can occur simultaneously and impact on crop development and yield. They are both known to affect catabolism, with rather opposite effects: inhibition of glycolysis and higher glycolytic fermentative flux, respectively. But surprisingly, the effect of their combination on plant metabolism has never been examined precisely. Here, we applied a combined treatment (K availability and waterlogging) to sunflower (Helianthus annuus L.) plants under controlled gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 63 publications
5
45
0
Order By: Relevance
“…Changes in organic acids were accompanied by a modification of amino acid metabolism, with a decrease in asparagine and serine, and in the content of alanine aminotransferase. Accordingly, we previously showed that waterlogging inhibited N assimilation in leaves (Cui et al ., ). It is worth noting that at high K, waterlogging was also associated with generally less amino acids in rachis, suggesting an inhibition of N assimilates export from leaves (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in organic acids were accompanied by a modification of amino acid metabolism, with a decrease in asparagine and serine, and in the content of alanine aminotransferase. Accordingly, we previously showed that waterlogging inhibited N assimilation in leaves (Cui et al ., ). It is worth noting that at high K, waterlogging was also associated with generally less amino acids in rachis, suggesting an inhibition of N assimilates export from leaves (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…There are many experimental works in the literature that show how a single abiotic stress can affect N uptake and assimilation at the physiological, biochemical, but also at gene expression level (Hemon et al, 1990;Mungur et al, 2005;Ashraf et al, 2018). However, very little information can be found about how the combination of two or more abiotic stresses may affect this important metabolic process (Cui et al, 2019). In recent years, an increase in the experiments in the field of abiotic stress combination has been observed, most probably due to the current undeniable effects of climate change on our agriculture and to the fact that in nature, abiotic stresses always act in combination.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are very little information about the effect of abiotic stress combination on the N uptake and assimilation pathway (Cui et al, 2019). Thus, in order to identify agronomic strategies that can be used to fight against the consequences of climate change in crops, detailed studies related to nitrogen metabolism should be developed at the physiological, biochemical, and molecular levels, which is also the primary metabolism related to growth and production in plants.…”
Section: Introductionmentioning
confidence: 99%
“…That is, quite counter‐intuitively, K + deficiency implies an extra demand in negative charges to reach electro‐neutrality, which is met by accumulated organic and amino acids (Armengaud et al, ). The excess of positive charges mostly comes from the considerable increase in Ca 2+ (up to twofold increase) and Mg 2+ (more than twofold) in oil palm and sunflower (Cui, Abadie, et al, ; Cui, Davanture, et al, ). Under K + deficiency, there is also an increase in the difference between Ca 2+ and the sum Mg 2+ + K + (of about 0.4 mmol positive charges g −1 DW in Figure ).…”
Section: Putrescine and Regulation Of Cation Transport And Balancementioning
confidence: 99%
“…This still needs to be tested under K + deficiency, based on large amounts of putrescine accumulated naturally. However, metabolomics analyses have suggested that the increased CO 2 release under K + deficiency is not associated with a higher ATP production but rather reflects lower efficiency of the TCAP when K + is limiting enzymatic activity (Cui, Abadie, et al, ). Also, it should be noted that mitochondrial carbonic anhydrase, which might play an important role in anaplerosis (conversion of catabolic CO 2 into bicarbonate), is inhibited with a high affinity (low K i ) by spermine and spermidine, while putrescine has no effect (Carta et al, ).…”
Section: Roles Of Putrescine In Mitochondriamentioning
confidence: 99%